Implementation Of Automatic Hydroponic System Design For Shallot (Allium Ascalonicum L.) Cultivation And Cost Analysis Simulation - Annisa Nur Rachmawaty; Sugeng Triyono; Siti Suharyatun; Mareli Telaumbanua (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Hydroponic shallot cultivation is one way to increase shallot production on marginal land. To support the cultivation, this research was designed that aimed to develop an automatic hydroponic system, simulation of cost analysis, and profit prediction on shallot cultivation.The study was conducted by arranging a hydroponic design with a height of 100 cm, length 3 m, and width of 60 cm. The growth media is made from husk charcoal with a depth of 15 cm.114 cloves of shallots are sown and moved after the buds develop about 5 cm, a distance of 10x15 cm. The research parameters included pH, EC, air content, and plant growth. Three scenarios of the hydroponics systems were simulated to elaborate cost and profit estimation. The three scenarios included scaling up the cultivation beds, ten year cultivation, and productivity from three types of hydroponics modules. The results showed that during hydroponics cultivation of shallot, EC of nutrient solution was elevated to the last level of 3106 μS/cm, while pH was found to be 7.58. The control system is able to activate the pump with 100% accuracy. The yield of the shallot was 0.0154 kg/m2 with average tuber diameter of 10-15 mm.  This production was suboptimal, yet profit and cost comparisons could be clearly described through the simulations of three types of hydroponics modules.  The results of the simulation of economic analysis, the highest B / C ratio obtained from the use of hydroponics on land is 1.53. Keywords: cost and profit analysis, hydroponics cultivation, nutrition solution, shallot